Teachers' beliefs on teachers' efficacy and teachers' behaviour in the classroom / Nor Aizah Nayan - Nayan, Nor Aizah (2015)
From Bandura's definition of self-efficay emerged a definition of teacher efficacy as a "teacher's judgments of their ability to organize and accomplish specific teaching tasks in order to produce the desired achievement of student outcomes (Tschannen-Moran & Woolfolk Hoy, 2001). Teachers' sense of efficacy has been found to be related to the actual teacher behaviour in classroom practices. Teachers with highly efficacious for teaching are likely perceived positive attitudes in managing their classes successfully (Henson, 2001).Efficacious teachers tend to exhibit high enthusiasm in teaching-learning activity, show strong commitment and positive attitudes about teaching, more open to educational reforms as well as in implementing and experimenting new teaching methods (Guskey, 1998; Stein & Wang, 1998). Therefore, this study was conducted with the aim to discover the teachers' beliefs on teacher efficacy and teacher behaviour in the classroom. A total of 120 secondary school teachers in Petaling Utama District were selected by using simple random method and 97 teachers responded to the questionnaire. This study employed descriptive, correlation research design. The data were collected using a questionnaire and open-ended questions.The quantitative data were statically analyzed using SPSS version 21 while the open-ended questions were analyzed using thematic analysis. The three dimensions of teacher efficacy were studied: efficacy of student engagement, efficacy of instructional strategies and efficacy of classroom management. The findings revealed that teachers are mostly perceived sense of efficacy at high level for each dimension. The following finding reported that the respondents exhibit positive perceptions towards the three dimensions of teacher efficacy. The study also explores the level of teachers' beliefs on teacher behaviour from the perspectives of behaviour management and instructional management. The findings showed that most teachers are having high belief on teacher behaviour in terms of behaviour management and instructional management. The following finding reported the respondents' exhibits positive perceptions towards behaviour management and instructional management. The findings of this study imply the importance of self-efficacy regarding its powerful influence on teacher effectiveness and therefore is hoped to contribute useful insights of the teachers' beliefs on teacher efficacy and teacher behaviour as well as the teaching process.